PENGARUH PROFITABILITAS, LIKUIDITAS, TANGIBILITY, PERTUMBUHAN DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2015 - 2019 - Celina Geraldine; Made Irma Lestari (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2022)
This research was conducted to analyze the factors that affect the capital structure of companies in the consumer goods sector that have been listed on the IDX and operated in the 2015 – 2019 period. There is a very drastic decline in the debt to equity ratio in the consumer goods sector compared to the other 8 sectors which available on the IDX. In the 2015 – 2019 period, the debt to equity ratio in the consumer goods sector increased and tends to be stable. The population in this study are companies in the consumer goods sector listed on the Indonesia Stock Exchange for the period 2015 – 2019. The sampling method used in this study is a purposive sampling method so as to produce 27 companies that can be used as objects in this study. The variables used in this study are: the independent variable profitability (ROA), current ratio (CR), tangibility (TANG), company growth (Growth), company size (Size) and the dependent variable debt to equity ratio (DER). The results of this study indicate that profitability, liquidity, tangibility, growth, and firm size have a partial and significant effect on the capital structure, and the results of this study also show that profitability, liquidity, tangibility, growth, and firm size have a simultaneous and significant effect on the structure. capital.